Case Report: Autoimmune Psychosis in Chromosome 22q11.2 Deletion Syndrome - Ciano-Petersen, Nicolás Lundahl; Hamad-Cueto, Omar; Drissi-Reyes, Hania; Doña-Díaz, Álvaro; García-Martín, Guillermina (Frontiers in Immunology, 2021)
Chromosome 22q11.2 deletion syndrome (22q11DS) is characterized by congenital cardiac abnormalities, hypoplastic thymus, palatal abnormalities, and hypocalcemia, although other clinical features are frequent such as autoimmune and psychiatric disorders. One-third of the patients have psychotic disorders, frequently followed by developmental regression and long-term cognitive disturbances. Despite humoral and cellular immunodeficiency are common in 22q11DS, it is associated with an increased prevalence of autoimmune disorders such as idiopathic thrombocytopenic purpura and juvenile idiopathic arthritis, likely due to immune dysregulations associated with thymic abnormalities, which plays a major role in self-tolerance. We report an unique case of a 14-year-old girl with 22q11DS that presented with subacute psychotic symptoms, intolerance to antipsychotics, CSF pleocytosis, and EEG abnormalities, that was successfully treated with empiric immunotherapy after fulfilling criteria for probable seronegative autoimmune encephalitis and probable autoimmune psychosis. The autoimmune etiology of these clinical features of 22q11DS has never been postulated despite the predisposition of this syndrome to present autoimmune disorders. We suggest the systematic evaluation with serum and CSF neuronal antibodies, MRI, and EEG of patients with 22q11DS that develop subacute psychotic symptoms or rapidly progressive cognitive decline. Early immunomodulatory therapies should be carefully considered if criteria of probable autoimmune psychosis or possible autoimmune encephalitis are fulfilled, as it may prevent long-term disabilities. Further studies are required to assess the autoimmune origin of psychosis and cognitive impairment associated with 22q11DS.